Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1371/journal.pone.0191635
|View full text |Cite
|
Sign up to set email alerts
|

The impact of stillbirth on bereaved parents: A qualitative study

Abstract: PurposeTo explore the lived experiences and personal impact of stillbirth on bereaved parents.MethodsSemi-structured in-depth interviews analysed by Interpretative Phenomenological Analysis (IPA) on a purposive sample of parents of twelve babies born following fetal death at a tertiary university maternity hospital in Ireland with a birth rate of c8,500 per annum and a stillbirth rate of 4.6/1000.ResultsStillbirth had a profound and enduring impact on bereaved parents. Four superordinate themes relating to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 31 publications
4
65
0
5
Order By: Relevance
“…The use of avoidance strategies led to the suppression of emotions and the emergence of tensions in the couple due to differences in coping between the sexes (Gopichandran et al, ; Lafarge et al, ; Nuzum, Meaney, & O'Donoghue, ). Attempts not to remember, see, talk, or experiment generated ignorance about certain aspects of the loss in parents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of avoidance strategies led to the suppression of emotions and the emergence of tensions in the couple due to differences in coping between the sexes (Gopichandran et al, ; Lafarge et al, ; Nuzum, Meaney, & O'Donoghue, ). Attempts not to remember, see, talk, or experiment generated ignorance about certain aspects of the loss in parents.…”
Section: Resultsmentioning
confidence: 99%
“…This meant that some of them later regretted not being present during the process (Leichtentritt & Mahat‐Shamir, ):
I think [partner] had a lot closer connection to him than I had, because I suppose I see my time with him as, when he was born to when he was buried… I remember thinking he's my son but he's not (very upset). Father (Nuzum et al, ).
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, women were able to recall vivid memories of their experiences even in the context of the passing of several years. Such vivid memory recall is not unexpected given the traumatic experience of stillbirth . Therefore, results of this study offer early insights that specifically focus upon Aboriginal and Torres Strait Islander women's decision‐making.…”
Section: Discussionmentioning
confidence: 72%
“…Because of gender inequities and imbalanced power dynamics with reproductive decision-making in marital relationships that was expressed by many participants, we suggest that involvement of men is critical to any intervention to promote healthy birth spacing in this population. Qualitative studies examining couples after stillbirth have found this experience is deeply shared between a woman and her partner, sometimes in a way that isolates them from the community [ 26 ]. This experience has also been shown to either have a positive or negative impact on the couples’ relationship [ 27 ].…”
Section: Discussionmentioning
confidence: 99%